Hand gesture-based recognition for interactive Human Computer using tenser-flow - Sangeeta Kumari , Shubham Mathesul , Parth Shrivastav , Ayush Rambhad (International Journal of Advanced Science and Technology, 2020)
Today’s modern era has been a witness of ever-increasing hand gestures-controlled computer, laptop and other electronics appliances-based applications. Image-based hand gesture recognition systems are very easy, simple and economical to use as these gesture-controlled applications does not involve any additional hardware. These applications mainly rely on inbuilt cameras. Such remote recognition is very unique and heavily influenced by its performance factors such as image processing, illumination conditions, objects interference, view of source input etc. Advantage of gesture recognition systems is that no physical contact is required between user and the gesture recognition-enabled device. Systems allows to interact with the interface and control devices using simple hand gestures. Also, gesture recognition technology saves crucial time. These systems are not only pleasant to implement in daily life but also helpful to help people having disabilities, these systems could also be packed together with IOT devices for relevant usage. Using gesture recognition system security and integrity could also be identified and boosted.